An Integrated Model of Career Change. - Rhodes, Susan R.; Doering, Mildred (Academy of Management Review, 1983)
Career change research has suffered from the absence of a comprehensive theoretical framework. The proposed model of career change is based on career change research and previously tested turnover theory. Both the determinants and process of career change are explained by the model. Longitudinal panel studies are suggested for testing of the model.